Dark matter credit: The development of peer-to-preer lending and banking in France - Hoffman, Philip T.; Poster-Vinay, Gilles; Rosenthal, Jean-Laurent (New Jersey Princeton University Press, 2019)
Dark Matter Credit traces how this extensive private network outcompeted banks and thrived prior to World War I$1 (Bnot just in France but in Britain, Germany, and the United States$1 (Buntil killed off by government intervention after 1918. Overturning common assumptions about banks and economic growth, the book paints a revealing picture of an until-now hidden market of thousands of peer-to-peer loans made possible by a network of brokers who matched lenders with borrowers and certified the borrowers$1 (Bcreditworthiness.s